(untitled) (Journal of Parents and Teachers, 2025)
Can a small Baltic country inspire a major educational transformation in Spain? This article explores the case of Estonia as an international benchmark in education, highlighting its key success factors: stability, valued teachers, effective use of technology, and genuine equity. In contrast, it analyzes the persistent challenges of the Spanish system and proposes six concrete ideas for progress. This is not about imitation, but reflection: education can improve when we place our bets on people, coherence, and a long-term vision.